Dementia in Africa: Current evidence, knowledge gaps, and future directions - (:unkn) unknown (My University, 2021)
In tandem with the ever-increasing aging population in low and middle-income countries, the burden of dementia is rising on the African continent. Dementia prevalence varies from 2.3% to 20.0% and incidence rates are 13.3 per 1000 person-years with increasing mortality in parts of rapidly transforming Africa. Differences in nutrition, cardiovascular factors, comorbidities, infections, mortality, and detection likely contribute to lower incidence. Alzheimer's disease, vascular dementia, and human immunodeficiency virus/acquired immunodeficiency syndrome-associated neurocognitive disorders are the most common dementia subtypes. Comprehensive longitudinal studies with robust methodology and regional coverage would provide more reliable information. The apolipoprotein E (APOE) ε4 allele is most studied but has shown differential effects within African ancestry compared to Caucasian. More candidate gene and genome-wide association studies are needed to relate to dementia phenotypes. Validated culture-sensitive cognitive tools not influenced by education and language differences are critically needed for implementation across multidisciplinary groupings such as the proposed African Dementia Consortium.
Keywords: African Research